Akibat Hukum Penggunaan Logo Perusahaan PT Pertamina (Persero) oleh Pelaku Usaha Penjual Bahan Bakar Minyak Pertamini Di Kota Denpasar - Kadek Dewi Darmayanti; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2021)
The very high demand for fuel oil in Denpasar is considered as a business opportunity that provides great benefits In the business activity of selling First Oil Fuel business actors use the logo belonging to PT Pertamina to attract consumers The use of the same logo as PT Pertamina is not justified because it does not have a license or license from the trademark owner The research method in this writing uses empirical research The author discusses two legal issues namely the legality of the use of the PT Pertamina (Persero) against the logo of the fuel oil seller trading business in Denpasar City and the sanctions imposed on the business actor selling the Pertamina oil fuel Based on the results of the data obtained it shows that Pertamini does not have a permit from PT Pertamina to use the logo and most of the Pertamini business actors do not have a business license so that the Pertamina business actors can be subject to a maximum imprisonment of 5 (five) years and / or a maximum fine of IDR 2 000 000 000 00 (two billion rupiah) 100 paragraph (1) of Law Number 20 of 2016 concerning Marks and Geographical Indications.